Developing an Android-Based Application for Arabic Grammar Learning Aligned with the Common European Framework of Reference (CEFR) - Nurdianto, Talqis; Zainuddin, Ghazali; Huda, Nurul; Amrulloh, M. Afif (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2025)
This research aims to develop an Arabic educational app that complies with the Common European Framework of Reference for Languages (CEFR) and can be downloaded from the Playstore. In addition, the study seeks to evaluate the authenticity, practicality, and effectiveness of Arabic language learning resources on the Android platform in accordance with CEFR standards. The approach taken in this application adheres to the research and development strategy known as the ADDIE model, which consists of five phases: analysis, design, development, implementation, and evaluation. This technique is applied to improve language skills by encouraging users to deduce correct answers using images, vocabulary, phrases, dialogues, grammar lessons, practice activities, quizzes, and puzzles presented in Arabic. All entry-level Arabic learning materials will be gathered in an application named